Potential effects of cannabinoids on audiovestibular function: A narrative review - Guerra, Joaquin; Naidoo, Vinogran; Cacabelos, Ramon (Frontiers in Pharmacology, 2022)
The growing interest in the development of drugs that target the endocannabinoid system has extended to conditions that affect the audiovestibular pathway. The expression of cannabinoid (CB) receptors in that pathway has been widely demonstrated, indicating a therapeutic potential for drug development at this level. These medications may be beneficial for conditions such as noise-induced hearing loss, ototoxicity, or various forms of vertigo of central or peripheral origin. The therapeutic targets of interest include natural or synthetic compounds that act as CB1/CB2 receptor agonists/antagonists, and inhibitors of the endocannabinoid-degrading enzymes FAAH and MAGL. Furthermore, genetic variations implicated in the response to treatment and the development of related disorders such as epilepsy or migraine have been identified. Direct methods of administering these medications should be examined beyond the systemic strategy.